Transforming Islamic Higher Education: Integrating Islamic Values and Digital Technology at UIN Siber Cirebon - Firdaus, Slamet; Suwendi, Suwendi; Nafi’a, Ilman; Gumiandari, Septi; Huriyah, Huriyah; Juanda, Anda (Jurnal Ilmiah Peuradeun, 2025)
The relationship between Islam and science remains a critical issue, particularly within the institutional transformation of Islamic higher education (PTKI) in Indonesia, where universities face the challenge of digitalization while maintaining their religious-epistemological identity. This study examined the strategies of UIN Siber Syekh Nurjati Cirebon to integrate Islamic and scientific knowledge. Using a qualitative methodology, data were collected through in-depth interviews, document analysis, and field observations with faculty, administrators, and students. The findings revealed four strategies: (1) a dialogical and dialectical approach that maintained epistemological integrity between Islam and science; (2) integration of ethics-based knowledge grounded in maqasid al-shariah; (3) an interdisciplinary curriculum combining Islamic and scientific disciplines; and (4) innovations contextualized in locality within cultural and religious traditions. The research proposed the “Muhsin Sejati” framework, an innovative model that distinguishes itself from earlier integration theories by uniquely grounding technological advancements in ethical and spiritual values. This model supported the development of graduates who were technically proficient, ethically responsible, and spiritually conscious. The research contributed to the theory of integrated Islamic education by operationalizing abstract concepts into institutional practices and offers global insights into value-driven educational models. Further studies are recommended to investigate the scalability and long-term effectiveness of the Muhsin Sejati model in various educational contexts.